Development of a population pharmacokinetics and pharmacodynamics model of glucarpidase rescue treatment after high-dose methotrexate therapy - Fukaya, Yutaka; Kimura, Toshimi; Hamada, Yukihiro; Yoshimura, Kenichi; Hiraga, Hiroaki; Yuza, Yuki; Ogawa, Atsushi; Hara, Junichi; Koh, Katsuyoshi; Kikuta, Atsushi; Koga, Yuhki; Kawamoto, Hiroshi (Frontiers in Oncology, 2023)
Introduction Glucarpidase (CPG2) reduces the lethal toxicity of methotrexate (MTX) by rapid degradation. Methods In this study, a CPG2 population pharmacokinetics (popPK) analysis in healthy volunteers (phase 1 study) and a popPK-pharmacodynamics (popPK-PD) analysis in patients (phase 2 study, n = 15) who received 50 U/kg of CPG2 rescue for delayed MTX excretion were conducted. In the phase 2 study, the first CPG2 treatment at a dose of 50 U/kg was intravenously administered for 5 min within 12 h after the first confirmation of delayed MTX excretion. The second dose of CPG2, with a plasma MTX concentration >1 μmol/L, was administered to the patient more than 46 h after the start of CPG2 administration. Results The population mean PK parameters (95% CI) of MTX, obtained from the final model post hoc, were estimated as follows: CLrMTX = 2.424 L/h (95% CI: 1.755–3.093), VcMTX = 12.6 L (95% CI: 10.8–14.3), VpMTX = 2.15 L (95% CI: 1.60–2.70), and α = 8.131 x 105 (4.864 x 105-11.398 x 105). The final model, including covariates, was CLrMTX (L/h): 3.248 x Body Weight/Serum creatinine/60 (CV 33.5%), VcMTX (L): 0.386 x Body Weight/body surface area (CV 29.1%), VpMTX (L):3.052 x Body Weight/60 (CV 90.6%), and α (L/h): 6.545 x 105 (CV 79.8%). Discussion These results suggest that the pre-CPG2 dose and 24 h after CPG2 dosing were the most important sampling points in the Bayesian estimation of plasma MTX concentration prediction at 48 h. These CPG2-MTX popPK analysis and Bayesian estimation of rebound in plasma MTX concentrations are clinically important to estimate >1.0 μmol/L 48 h after the first CPG2 dosing. Clinical trial registration https://dbcentre3.jmacct.med.or.jp/JMACTR/App/JMACTRS06/JMACTRS06.aspx?seqno=2363, identifier JMA-IIA00078 and https://dbcentre3.jmacct.med.or.jp/JMACTR/App/JMACTRS06/JMACTRS06.aspx?seqno=2782, identifier JMA-IIA00097.